Lipidomics Reveals the Therapeutic Effects of EtOAc Extract of Orthosiphon stamineus Benth. on Nephrolithiasis - Chao, Yufan; Gao, Songyan; Li, Na; Zhao, Hongxia; Qian, Yong; Zha, Haihong; Chen, Wei; Dong, Xin (Frontiers in Pharmacology, 2020)
Background: Nephrolithiasis is a systemic metabolic disease with a high prevalence worldwide and is closely related to lipid-mediated oxidative stress and inflammation. Orthosiphon stamineus(OS) is a traditional medicinal herb mainly containing flavonoids, caffeic acid derivatives, and terpenoids, which has the effect of treating urinary stones. However, the active ingredients of OS for the treatment of kidney stones and their regulatory mechanisms remain unknown. As a powerful antioxidant, flavonoids from herbs can mitigating calcium oxalate stone formation by scavenging radical. Thus, this work focused on EtOAc extract of OS (EEOS, mainly flavonoids ) and aimed to reveal the potential intrinsic mechanism of EEOS in the treatment of kidney stones disease. Methods: Firstly, 75% ethanol extract of OS was further extracted with EtOAc to obtain EtOAc extract containing 88.82% flavonoids. Secondly, the extract was subjected to component analysis and used in animal experiments. Then, an untargeted lipidomics based on ultra high performance liquid chromatography coupled with TripleTOF 5600 mass spectrometer (UPLC-QTOF-MS) was performed to test the lipid changes of kidneys in the control group, model group and EEOS treatment groups. Finally, multivariate statistical analysis was used to identify differences between the lipid profiles of mice in the model group and the EEOS group. Results: 51 lipid metabolites were significantly different between the mice in the model group and the EEOS intervention group, including glycerophosphocholines, glycerophosphoethanolamines, glycerophosphoinositols, and glycerophosphoglycerols. And the composition of glycerophospholipids-esterified ω-3 polyunsaturated fatty acids and glycerophospholipid subclasses in the kidneys of the EEOS group significantly changed compared to model group. Conclusions: The EEOS can inhibit the stones formation by improving oxidative stress and inflammation mediated by glycerophospholipid metabolism. This study reveals the potential mechanism of EEOS for kieney stones treatment at the lipid molecule level, providing a new direction for further study of the efficacy of OS.